2015
DOI: 10.1590/s1980-65742015000100001
|View full text |Cite
|
Sign up to set email alerts
|

Critical velocity estimates lactate minimum velocity in youth runners

Abstract: In order to investigate the validity of critical velocity (CV) as a noninvasive method to estimate the lactate minimum velocity (LMV), 25 youth runners underwent the following tests: 1) 3,000m running; 2) 1,600m running; 3) LMV test. The intensity of lactate minimum was defined as the velocity corresponding to the lowest blood lactate concentration during the LMV test. The CV was determined using the linear model, defined by the inclination of the regression line between distance and duration in the running te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Despite the fact that several studies followed the original 8 min recovery (Bacon and Kern, 1999; Carter et al, 1999a,b, 2000; MacIntosh et al, 2002; Dantas De Luca et al, 2003; Ribeiro et al, 2003; Zagatto et al, 2004, 2013, 2014; Simões et al, 2005, 2009; Hiyane et al, 2006; Altimari et al, 2007, 2010; Azevedo et al, 2007; Silva et al, 2007; Pardono et al, 2008; Johnson et al, 2009; Johnson and Sharpe, 2011; Mota et al, 2011; Barbieri and Gobatto, 2013; Camargo et al, 2013; Mezzaroba and Machado, 2013; Miranda et al, 2013; Miyagi et al, 2013, 2015; Campos et al, 2014; Messias et al, 2015), a myriad of recovery manipulations is also observed, especially regarding the recovery type and intensity (Davison et al, 2000; Smith et al, 2002; Rotstein et al, 2007; Silva et al, 2007; Sotero et al, 2007, 2009, 2011; Knoepfli-Lenzin and Boutellier, 2011; Vicente-Campous et al, 2014; Browne et al, 2015). Some attention has been given to this phase due to its potential LMI influence.…”
Section: Can the Lmt Be Influenced By Methodological Aspects?mentioning
confidence: 99%
“…Despite the fact that several studies followed the original 8 min recovery (Bacon and Kern, 1999; Carter et al, 1999a,b, 2000; MacIntosh et al, 2002; Dantas De Luca et al, 2003; Ribeiro et al, 2003; Zagatto et al, 2004, 2013, 2014; Simões et al, 2005, 2009; Hiyane et al, 2006; Altimari et al, 2007, 2010; Azevedo et al, 2007; Silva et al, 2007; Pardono et al, 2008; Johnson et al, 2009; Johnson and Sharpe, 2011; Mota et al, 2011; Barbieri and Gobatto, 2013; Camargo et al, 2013; Mezzaroba and Machado, 2013; Miranda et al, 2013; Miyagi et al, 2013, 2015; Campos et al, 2014; Messias et al, 2015), a myriad of recovery manipulations is also observed, especially regarding the recovery type and intensity (Davison et al, 2000; Smith et al, 2002; Rotstein et al, 2007; Silva et al, 2007; Sotero et al, 2007, 2009, 2011; Knoepfli-Lenzin and Boutellier, 2011; Vicente-Campous et al, 2014; Browne et al, 2015). Some attention has been given to this phase due to its potential LMI influence.…”
Section: Can the Lmt Be Influenced By Methodological Aspects?mentioning
confidence: 99%
“…The maximal lactate steady state (MLSS) is considered a physiological benchmark for the evaluation and prescription of endurance training intensities 1 . A method used to estimate MLSS is the blood lactate concentrations (BLa) 2 , called lactate threshold (LT), determined at the highest constant workload, in which during a maximal incre-mental protocol 3 is achieved a maximum balance between lactate production and their clearance rates in the blood [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…This practical application of CS can be observed most commonly in swimming, where the calculation of CS is frequently utilized for youth training and performance [7,[11][12][13]. Application can also be found, although infrequent, in other sports e.g., running [14].…”
Section: Introductionmentioning
confidence: 99%